2021
DOI: 10.3390/ijms22147278
|View full text |Cite
|
Sign up to set email alerts
|

Impact of One-Carbon Metabolism-Driving Epitranscriptome as a Therapeutic Target for Gastrointestinal Cancer

Abstract: One-carbon (1C) metabolism plays a key role in biological functions linked to the folate cycle. These include nucleotide synthesis; the methylation of DNA, RNA, and proteins in the methionine cycle; and transsulfuration to maintain the redox condition of cancer stem cells in the tumor microenvironment. Recent studies have indicated that small therapeutic compounds affect the mitochondrial folate cycle, epitranscriptome (RNA methylation), and reactive oxygen species reactions in cancer cells. The epitranscripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Antioxidant function can also contribute to tumorigenesis by suppressing cell death during chemotherapy and radiation therapy. Antioxidant function is activated by the trans‐sulfuration pathway of one‐carbon metabolism, which is involved in various S‐adenosyl methionine‐induced methylation reactions 22 …”
Section: Lipid‐reactive Oxygen Species Can Induce Ferroptosis In Pdac...mentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidant function can also contribute to tumorigenesis by suppressing cell death during chemotherapy and radiation therapy. Antioxidant function is activated by the trans‐sulfuration pathway of one‐carbon metabolism, which is involved in various S‐adenosyl methionine‐induced methylation reactions 22 …”
Section: Lipid‐reactive Oxygen Species Can Induce Ferroptosis In Pdac...mentioning
confidence: 99%
“…Antioxidant function is activated by the trans‐sulfuration pathway of one‐carbon metabolism, which is involved in various S‐adenosyl methionine‐induced methylation reactions. 22 …”
Section: Lipid‐reactive Oxygen Species Can Induce Ferroptosis In Pdac...mentioning
confidence: 99%
“…In addition, a biochemical study on T cell function [38] and a clinical investigation on gastrointestinal cancer [28] noted large changes in the gene expression of genes in the serine hydroxymethyltransferase (SHMT)2 to MTHFD2 metabolic pathway. A study on immune cells with the antioxidant N-acethylcycteine indicated that the activation of T cells requires both the generation of a one-carbon unit and redox defense (Figure 3) [39], suggesting that T cell activation is linked to the trans-sulfuration pathway in one-carbon metabolism [4] and that there is a great need for developing MTHFD2-specific reagents [25]. Nonetheless, one-carbon metabolism and drug discovery in cancer stem cells (i.e., a fraction of stemness-possessing cancer cells in whole-tumor tissues) remains to be completely understood.…”
Section: Methionine and One-carbon Metabolism Pathway In Cancermentioning
confidence: 99%
“…Although the tumor mutation burden is defined by the total number of somatic mutations in cancer cell DNA, research has elucidated that metabolism plays a fundamental role in cancer biology in TME [3]. Research has demonstrated that interactions among cancer cells, immune cells, and CAFs emerge via metabolites based on biomass and the energy production of one-carbon metabolism via metabolites based on biomass and the energy production of one-carbon metabolism (Figure 1) [4]. This mechanism is an attractive target for efficient cancer drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies suggested that RNA methylation contributed to PDAC and other elements of tumor heterogeneity(25). RNA modification reportedly exerted a critical function in transcriptional regulation(25), translational regulation(25), A-to-I editing(89), chemoradiation therapy resistance(53,77), miRNA and ncRNA signaling(90), metabolic dependencies(91), and epigenetic regulation(92). These mechanisms are responsible for the orchestration of the control of proliferation, migration, and angiogenesis of CSC-like cells, for stem cell maintenance and differentiation, as well as for evasion of antitumor immunogenic cells(93).…”
mentioning
confidence: 99%